TRADISI PEMBELAJARAN KITAB KUNING DALAM KURIKULUM PESANTREN - Nelly Izmi (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2022)
The Yellow Book (also known as “Kitab Kuning”) is an important factor that characterizes Pondok Pesantren (Islamic boarding schools). The Yellow Book is functioned by Pondok Pesantren as a reference whichits content is unquestionable. The fact that the Yellow Book was written a long time ago and continues to be used from time to time shows that the Yellow Book has been tested for its truth in a long history. This study aims to reveal the Yellow Book learning method, skills in the Yellow Book teaching, and assessment in the Yellow Book learning book. The research method used is qualitative with the type of library research. The results of this study indicate that the Yellow Book learning method used is Wetonan/Bandongan, Sorogan, memorization, mudzakarah, majelis taklim, bahtsul kutub, fathul kutub, muqoronah. The skills in teaching the Yellow Book are: reading skills, translation skills, and understanding skills. Assessment of the Yellow Book is by: a. Testing the reading skills by asking students to read one by one. b. Testing the translation skills by asking students to read and translate before group discussions. c. Testingthe comprehension skills by asking students to explain the contents of the Yellow Book in front of the audience directly, if necessary, holding questions and answers.